ANALISIS KEPUASAN PENGGUNA SISTEM INFORMASI BERDASARKAN KUALITAS SISTEM, PERSEPSI KEGUNAAN DAN KUALITAS INFORMASI DI RSUD BOYOLALI - Nawang Adi Prasetyo; Heni (Jurnal Akuntansi dan Bisnis, 2025)
In the era of digital public services, accounting information systems are crucial for improving efficiency and accountability in healthcare institutions. However, the level of user satisfaction plays a critical role in determining the success of system implementation. To analyze the influence of information system quality, perceived usefulness, and information quality on user satisfaction with accounting information systems among employees at the Regional General Hospital (RSUD) in Boyolali is the primary goal for this study. A quantitative research design was adopted, incorporating data collection via survey methods. A total of 32 active users of SIMDA or Regional Financial Management Information System  participated by completing questionnaires. Multiple linear regression analysis was performed with the aid of SPSS 26. The findings of the study indicate that the variables of information system quality, perceived usefulness, and information quality collectively contribute significantly to user satisfaction with the accounting information system, with a contribution percentage of 87.6%. Partially, each of these variables also has a positive and significant influence. The remaining 12.4% is attributed to other factors beyond the scope of this study. This suggests that continuous improvement in system and information quality can play a crucial role in enhancing user satisfaction.